GENESIS INTERPRETATIONS OF THE DEFINITION OF ‘INVESTMENT’ - A. Snetkova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article discusses the economic nature of the investment and summarizes the theoretical approaches to the interpretation of the essence of the concept of "investment" as an economic category. A comparative analysis of the existing definitions carries out on the basis of a critical study of foreign and domestic researchers theories, shows their inseparable relationship with the capital. The question of investments at the macro and micro levels to implement them. Formulated author detailed definition of the category "investment".